DoriC 10.0: an updated database of replication origins in prokaryotic genomes including chromosomes and plasmids - Luo, Hao; Gao, Feng (Nucleic acids research, 2019)
Abstract DoriC, a database of replication origins, was initially created to present the bacterial oriCs predicted by Ori-Finder or determined by experiments in 2007. DoriC 5.0, an updated database of oriC regions in both bacterial and archaeal genomes, was published in the 2013 Nucleic Acids Research database issue. Now, the latest release DoriC 10, a large-scale update of replication origins in prokaryotic genomes including chromosomes and plasmids, has been presented with a completely redesigned user interface, which is freely available at http://tubic.org/doric/ and http://tubic.tju.edu.cn/doric/. In the current release, the database of DoriC has made significant improvements compared with version 5.0 as follows: (i) inclusion of oriCs on more bacterial chromosomes increased from 1633 to 7580; (ii) inclusion of oriCs on more archaeal chromosomes increased from 86 to 226; (iii) inclusion of 1209 plasmid replication origins retrieved from NCBI annotations or predicted by in silico analysis; (iv) inclusion of more replication origin elements on bacterial chromosomes including DnaA-trio motifs. Now, DoriC becomes the most complete and scalable database of replication origins in prokaryotic genomes, and facilitates the studies in large-scale oriC data mining, strand-biased analyses and replication origin predictions.